RASIO KEUANGAN YANG PALING BAIK UNTUK MEMPREDIKSI RETURN SAHAM : SUATU STUDI EMPIRIS PADA PERUSAHAAN MENUFAKTUR YANG TERDAFTAR DIBURSA EFEK JAKARTA - MEYTHI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2007)
This study aims to determine the best financial ratios in predicting stock return. there are 13 financial ratio (current ratio (cr), quick ratio (qr), current assets total assets (cata), debt ratio (dr), equity to total assets (eta), inventory turnover (arto), return on investement (roi), return on equity (roe), price earnings ratio (per), price book value (pbk) dan stock return (sr) categorized into five factors (liquidity/solvability factor, activity factor, profitability factor, capital market factor, and stock return) factor in predicting stock return. Data in this study are from manufacturing firms listed on the jakarta stock exchange during 200-2004. factor analysis is used to determine the best financial ratios in predicting stock return. The empirical result show that current ratio (cr) is the best financial ratio in prediciting stock return.